Nilai-Nilai Toleransi Antaretnis dalam Perspektif Hadis - Gintari, Ayu; Alwi, Zulfahmi; Tasbih, Tasbih (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore the values of inter-ethnic tolerance in the perspective of the Prophet Muhammad’s hadiths as an ethical foundation for Islamic social relations in multicultural societies. The recurrence of ethnic conflicts in Indonesia, such as those in Papua and Rempang, reflects a gap between Islam’s normative ideals and contemporary social realities. In this context, the research examines prophetic messages embedded in authentic hadiths that emphasize human equality regardless of race or ethnicity. Employing a thematic (maudhu‘i) approach, this study integrates both textual and contextual analyses of selected hadiths related to the principles of equality, solidarity, and the prohibition of tribal or ethnic fanaticism (‘ashabiyyah). To deepen the analysis, insights from the sociology of ethnicity and conflict are incorporated in order to construct a more comprehensive understanding of how these prophetic values are applied within the Indonesian social setting. The findings demonstrate that the Prophet consistently rejected all forms of ethnic superiority and upheld three central moral pillars of Islamic social ethics: equality, human solidarity, and social justice. These principles also serve as the foundation of wasathiyah, the Islamic doctrine of moderation characterized by balance, justice, and the rejection of all forms of extremism, including ethnic or tribal fanaticism, which may threaten social harmony. These prophetic values function as both spiritual and sociological mechanisms for preventing disintegration and strengthening social cohesion amid Indonesia’s cultural and ethnic diversity. The contextualization of wasathiyah and prophetic ethics within education, public policy, and intergroup discourse contributes to fostering religious moderation and developing a humanistic and inclusive Islamic interpretation that aligns with the realities of a multicultural nation.